If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + 4 = x + -13 Combine like terms: 2 + 4 = 6 6 = x + -13 Reorder the terms: 6 = -13 + x Solving 6 = -13 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 6 + -1x = -13 + x + -1x Combine like terms: x + -1x = 0 6 + -1x = -13 + 0 6 + -1x = -13 Add '-6' to each side of the equation. 6 + -6 + -1x = -13 + -6 Combine like terms: 6 + -6 = 0 0 + -1x = -13 + -6 -1x = -13 + -6 Combine like terms: -13 + -6 = -19 -1x = -19 Divide each side by '-1'. x = 19 Simplifying x = 19
| 7/8w=-2/3 | | x-12=-3-15 | | x-20=1-15 | | 144=x+2*x*6 | | 8+2t-6=9t+20-5t | | 6x^5-10x^4/2x^2 | | 9x-7x=-36 | | 78x-7= | | p+38=22 | | ln(x)+8=22 | | 17+5=x+3 | | x+x+27+4x-33=816 | | 2/9x10/12x18/25 | | 3.66=5.5x+3 | | 95=y/4-18 | | 3.33=5.5x+3 | | 21x^2+11x-2=0 | | 9x-5=4(3x-2) | | x^5*x= | | 7a+2=2a+4 | | 78/54 | | 400=70t-3t^2 | | 7-27/8 | | -4(-2x-7)6x-7= | | 2(3-m)-3m(m-3)=(6-2m)-3m | | -5x^3= | | 2(5xy-6)+4(8+3x)-6=0 | | 4x/9-8y=5 | | 297=(x+2)3x | | 20+4b-5a-ab= | | 2x+3y=49 | | (11x/4)=(2x/5) |